Effects of insulin, insulin-like growth factor-II, and nerve growth factor on neurite formation and survival in cultured sympathetic and sensory neurons - Recio-Pinto, E (J Neurosci, 1986)
Insulin and the insulin-like growth factors (IGFs) may directly affect the development of the nervous system. NGF, IGF-II, and insulin's effects on neurite formation and neuronal survival were studied in peripheral ganglion cell cultures from chick embryos. Neurite outgrowth was enhanced in a dose-dependent manner by insulin and IGF-II in sympathetic cell cultures. The half-maximally effective concentration, ED50, was about 0.4-0.6 nM for both polypeptides, and concentrations as low as 10 pM were active. However, in sensory neurons the ED50 for neurite outgrowth was about 30 nM for insulin and 0.1 nM for IGF-II, suggesting that these factors may have selective effects in different neuronal tissues. Neither serum nor the presence of non-neuronal cells was required for the response in sympathetic neurons. The specific anti- NGF antiserum inhibited the neurite outgrowth response to NGF but not to insulin nor IGF-II. Insulin and IGF-II additionally supported survival of sensory and sympathetic neurons; however, insulin was not as efficacious as NGF. The combination of high concentrations of NGF and insulin was no better than NGF alone in supporting sympathetic cell survival, or neurite outgrowth. This indicates that insulin acts on the same, or a subpopulation, of NGF-responsive neurons. These results support the hypothesis that insulin and its homologs belong to a broad family of neuritogenic polypeptides.